2007
DOI: 10.1124/mol.107.034041
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Activates an Angiogenic Pathway, Hypoxia Inducible Factor (HIF)-1-Vascular Endothelial Growth Factor, by Inhibiting HIF-Prolyl Hydroxylase: a Structural Analysis of Quercetin for Inhibiting HIF-Prolyl Hydroxylase

Abstract: We investigated a molecular mechanism underlying quercetinmediated amelioration of colonic mucosal injury and analyzed chemical structure contributing to the quercetin's effect. Quercetin up-regulated vascular endothelial growth factor (VEGF), an ulcer healing factor, not only in colon epithelial cell lines but also in the inflamed colonic tissue. VEGF derived from quercetin-treated colon epithelial cells promoted tube formation. The VEGF induction was dependent on quercetin-mediated hypoxia-inducible factor-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 32 publications
3
35
0
1
Order By: Relevance
“…Quercetin is known to chelate Fe 2þ (Leopoldini et al, 2006) and it has been suggested that the increase in HIF-1a is a direct result of this property (Jeon et al, 2007;Park et al, 2007;Triantafyllou et al, 2007). Fe 2þ is a cofactor for HPH, an enzyme which catalyses the hydroxylation of HIF-1a thus targeting it ultimately for degradation via the proteosome.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin is known to chelate Fe 2þ (Leopoldini et al, 2006) and it has been suggested that the increase in HIF-1a is a direct result of this property (Jeon et al, 2007;Park et al, 2007;Triantafyllou et al, 2007). Fe 2þ is a cofactor for HPH, an enzyme which catalyses the hydroxylation of HIF-1a thus targeting it ultimately for degradation via the proteosome.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin, which is a flavonol found in several varieties of berries at concentrations of up to 70-80 mg/kg dry wt., has been found to inhibit the growth and stimulate the apoptosis of cancer cells (14).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, quercetin inhibits HIF-1a protein synthesis under hypoxia in the human prostate cancer cell line LNCaP, colon cancer cell line CX-1, and breast cancer cell line SkBr3 [49]. However, under normoxia increases HIF-1a in the human colon epithelial cell lines HCT116 and SW620 [50], as well as HIF-1a/HIF-2a by impairing its degradation by PHDs in the human prostate adenocarcinoma cell lines LNCaP, DU-145 and PC-3 or HCT116 cells [50,51]. Genistein, another flavonoid and inhibitor of tyrosine kinases, completely blocks the synthesis of both HIF-1 subunits in human retinal pigment epithelium cells [52] as well as HIF-1 DNA-binding activity [53].…”
Section: Inhibition Of Hif-a Translationmentioning
confidence: 99%